2021
DOI: 10.1039/d1lc00375e
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker barcodes: multiplexed microfluidic immunohistochemistry enables high-throughput analysis of tissue microarray

Abstract: We present a multiplexed microfluidic immunohistochemistry (IHC) technology that enables high-throughput analysis of tissue microarrays (TMAs) using the patterns of biomarker barcodes, which consist of a series of expressed linear...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The ability of the probe to target cells is closely related to conditions such as probe concentration and incubation time [ 36 ]. For clarifying the conditions of use of the obtained magnetic fluorescent nanoprobes, we successively explored the effects of the amount of probe used, the total volume of incubation and the incubation time on the targeting efficiency of the probes.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the probe to target cells is closely related to conditions such as probe concentration and incubation time [ 36 ]. For clarifying the conditions of use of the obtained magnetic fluorescent nanoprobes, we successively explored the effects of the amount of probe used, the total volume of incubation and the incubation time on the targeting efficiency of the probes.…”
Section: Resultsmentioning
confidence: 99%
“…Several types of cancers are affected by MMPs in different ways [24,25]. As of this writing, a total of 24 MMPs have been discovered (MMP1, 2, 3, 4, 5,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,23, 23a/23b, 24, 25, 26, 27, and 28). Liu et al reported that lymph node metastases, microvessel density, and an advanced TNM stage were all linked to ESCC patients with elevated MMP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to perform prognosis studies on cancer patients using microarray techniques in addition to identifying genes associated with various diseases and potential antitumor medication targets [ 9 , 10 ]. In addition, microarray techniques have an important ability in analyzing the associations between the expression of functional genes and their modulation [ 11 , 12 ]. In the field of clinical research, they are also responsible for contributing ideas for the diagnosis and treatment of specific disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from feasibility studies have been encouraging, and more research could be done in this area to translate emerging technologies to clinical practice. Recently, a high throughput system to analyse tissue microarrays of breast cancer samples using multiplexed microfluidic IHC to generate biomarker barcodes have been developed [100]. The biomarker barcode of breast cancer patient-derived tissue microarrays was compared to traditional method of breast cancer diagnosis, thus opening the possibility of high-throughput screening with diagnostic capability.…”
Section: Future Potential Application Of Ctas In Screening Workflow In Clinical Practicementioning
confidence: 99%